FIL–JAWAB–NATIJAH AS AN ALTERNATIVE FRAMEWORK FOR LEGAL INTERPRETATION OF QURANIC NARRATIVE VERSES: THE PERSPECTIVE OF IZZ AL-DIN IBN ABD AL-SALAM - Arifin, Mohamad Zaenal; Bahrul Hikam, Ahmad; Nurkholis (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2025)
Quranic narrative verses, in addition to serving as sources of spiritual, moral, and educational values, can also function as a medium for formulating legal principles. This article examines a model of interpreting Quranic narrative verses in Shajarat al-Maarif by Izz al-Din ibn Abd al-Salam. This study employs a qualitative method based on library research. The primary source of data is Shajarat al-Maarif, while secondary sources include classical Quranic commentaries, books, and scholarly articles relevant to the topic. The collected data are analyzed using content analysis techniques. The findings reveal that Ibn Abd al-Salam interprets Quranic narrative verses through a fil–jawab–natijah model, which is integrated with elements of Sufism, maqasid al-shariah, and usul al-fiqh in the process of deriving legal principles. Through this model, every human action (fil) is evaluated based on God’s response (jawab), which subsequently generates normative consequences (natijah) that can be generalized into legal maxims. From the narratives of the prophets—such as Prophet Yusuf, Musa, and Ibrahim—and the figure of Qarun, Ibn Abd al-Salam extracts legal principles including non-formal evidentiary procedures, the prioritization of public interest (maslahah), and prophetic ethics in the implementation of legal obligations (taklif). From the story of Qarun, he further emphasizes the importance of wealth redistribution, anti-greed ethics, and policies of economic justice. This study concludes that the fil–jawab–natijah model proposed by Ibn Abd al-Salam enriches the discourse of legal interpretation of Quranic narrative verses by offering an integrative and contextual approach.